2006
DOI: 10.1080/00207590500345963
|View full text |Cite
|
Sign up to set email alerts
|

Ego‐identity: Can it be reconstituted after a brain injury?

Abstract: Cognitive alterations are frequently observed and studied in persons who present with psychiatric and neurological disorders. Recently an increased number of investigations on the self and attendant processes have interested psychologists, psychiatrists, and neuropsychologists, particularly when a person has suffered brain damage that upsets their daily function in economic, social, personal, behavioural, and emotional ways. At the same time, many theories have been developed to explain the observable changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 23 publications
(22 reference statements)
1
8
0
Order By: Relevance
“…It has been reported that the terms self, sense of self, selfidentity, ego identity, personal identity, and identity are used fairly interchangeably in the literature, with no clear distinctions between them (Biderman et al, 2006;Coetzer, 2008); our findings concur with this viewpoint. For example, in the general psychology literature, the term self has been attributed with at least five distinct meanings (Leary & Tangney, 2012).…”
Section: Overview Of Findingssupporting
confidence: 93%
“…It has been reported that the terms self, sense of self, selfidentity, ego identity, personal identity, and identity are used fairly interchangeably in the literature, with no clear distinctions between them (Biderman et al, 2006;Coetzer, 2008); our findings concur with this viewpoint. For example, in the general psychology literature, the term self has been attributed with at least five distinct meanings (Leary & Tangney, 2012).…”
Section: Overview Of Findingssupporting
confidence: 93%
“…As a positive self-concept after neurological injury is associated with increased quality of life (Vickery et al, 2005) and reduced likelihood of Nordic Journal of Music Therapy 3 experiencing depressive symptoms (Carroll & Coetzer, 2011), effective reconstruction of an organized, compelling, and realistic identity is considered an important goal of rehabilitation (Biderman, Daniels-Zide, Reyes, & Marks, 2006). However, there are currently no evidenced-based treatments that can successfully address this important rehabilitation need.…”
Section: Self-concept and Acquired Neurological Impairmentsmentioning
confidence: 99%
“…The growing literature on identity after brain injury converges on two critical themes: (1) identity or sense of self is often shattered by the effects of the injury on the individual's abilities and roles, and (2) effective reconstruction of an organised, compelling, and reasonably realistic identity is central to the process of rehabilitation (Biderman, Daniels-Zide, Reyes, & Marks, 2006). Goals set by rehabilitation professionals for individuals with brain injury as well as strategies to achieve the goals may be rejected out of hand by the person simply on grounds that, "What you are proposing is not me!"…”
Section: Identity and Goal Setting After Brain Injurymentioning
confidence: 99%